Externalities and Macroprudential Policy - De Nicolo, Gianni; Favara, Giovanni; Ratnovski, Lev. (Washington, D.C. : International Monetary Fund, 2012)
This note overviews macroprudential policy options that have been proposed to address the systemic risks experienced during the recent financial crisis. It contributes to the policy debate by providing a taxonomy of macroprudential policies in terms of the specific negative externalities in the financial system that these policies are meant to address, and discusses their interrelations and some key implementation issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet